Vacuum CVD coatings Ta on target W plate of neutrons source - Borts, B.V.; Neklyudov, I.M.; Polyakov, Yu.I.; Rudenky, S.G.; Lukirsky, Yu.V.; Vorobyov, I.A.; Lopata, А.А. (Вопросы атомной науки и техники, 2019)
The paper presents data on the creation of a tungsten target, protected from corrosion under irradiation with a power of up to 100 kW. A protective coating of tantalum with a thickness of 250 µm was deposited on the surface of tungsten plates 66x66 mm, thickness 10; 6; 4; 3 mm. The coating has a solid-phase compound over the entire surface of tungsten and is hermetic. This was achieved by CVD (chemical vapor deposition) tantalum deposition in a vacuum of 2.66·10⁻² Pa on a plate surface heated to ~ 1700 K using the thermal dissociation reaction of tantalum pentachloride vapor. Such tungsten plates, equipped with tantalum coatings with desired properties, were used in the Neutron Source installation of the NSC KIPT.